Efficient Production of Polymyxin in the Surrogate Host Bacillus subtilis by Introducing a Foreign ectB Gene and Disrupting the abrB Gene - Park, Soo-Young (American Society for Microbiology, 2012)
In our previous study, Bacillus subtilis strain BSK3S, containing a polymyxin biosynthetic gene cluster from Paenibacillus polymyxa, could produce polymyxin only in the presence of exogenously added l-2,4-diaminobutyric acid (Dab). The dependence of polymyxin production on exogenous Dab was removed by introducing an ectB gene encoding the diaminobutyrate synthase of P. polymyxa into BSK3S (resulting in strain BSK4). We found, by observing the complete inhibition of polymyxin synthesis when the spo0A gene was knocked out (strain BSK4-0A), that Spo0A is indispensable for the production of polymyxin. Interestingly, the abrB-spo0A double-knockout mutant, BSK4-0A-rB, and the single abrB mutant, BSK4-rB, showed 1.7- and 2.3-fold increases, respectively, in polymyxin production over that of BSK4. These results coincided with the transcription levels of pmxA in the strains observed by quantitative real-time PCR (qRT-PCR). The AbrB protein was shown to bind directly to the upstream region of pmxA, indicating that AbrB directly inhibits the transcription of polymyxin biosynthetic genes. The BSK4-rB strain, producing high levels of polymyxin, will be useful for the development and production of novel polymyxin derivatives.